2020
DOI: 10.37268/mjphm/vol.20/no.3/art.841
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between General Health, Occupational Stress and Job Burnout in Nurses Working Shohadaye Kargar Hospital of Yazd

Abstract: Aim of this study is to determine levels of general health, occupational stress and burnout in nurses who are working in Shohadaye Kargar Hospital of Yazd. A cross- sectional study was conducted among nurses who are working in Shohadaye Kargar Hospital of Yazd in 2017-2018 years. The sample was randomly selected and total 200 nurses were enrolled to the study. The study instruments included Occupational stress questionnaire, Maslach Burnout Inventory and General Health Questionnaire. Collected Data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Participants in this study had high occupational stress scores. This outcome is consistent with the findings of various studies conducted during the COVID-19 pandemic (Fatemeh et al, 2020; Hummel et al, 2021; Said & El-Shafei, 2021). These outcomes could be due to the stressors imposed on nurses during the COVID-19 pandemic including the high workload, insufficient knowledge about the pathogen, direct contact with infected patients, and discomfort from prolonged wearing of personal protective equipment (Amro et al, 2022; Hummel et al, 2021; Zhang et al, 2020; Zhou et al, 2020).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Participants in this study had high occupational stress scores. This outcome is consistent with the findings of various studies conducted during the COVID-19 pandemic (Fatemeh et al, 2020; Hummel et al, 2021; Said & El-Shafei, 2021). These outcomes could be due to the stressors imposed on nurses during the COVID-19 pandemic including the high workload, insufficient knowledge about the pathogen, direct contact with infected patients, and discomfort from prolonged wearing of personal protective equipment (Amro et al, 2022; Hummel et al, 2021; Zhang et al, 2020; Zhou et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…The current study found a significant positive correlation between general health and occupational stress. This finding is congruent with a previous study which concluded that reducing occupational stress could improve the mental health of nurses (Fatemeh et al, 2020; Ta’an et al, 2020). Also, it is congruent with the study of Jordan et al (2016) which found that nurses with high stress had poor health outcomes and high health risk behaviors.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation